Relationship of Optimism, Pessimism, and Dysfunctional Career Thoughts in Breast Cancer Survivors from the Bahamas. Issue 1 (2nd January 2021) - Scott, Levette S; Zalaquett, Carlos P; Exum, Herbert; Kromrey, Jeffrey D; Ellerbrock, Cheryl R; Paxton, Raheem J.
ABSTRACT: A breast cancer diagnosis can lead to life-altering biopsychosocial changes and challenges for breast cancer survivors (BCS). Particularly salient is body image perception and its associated biopsychosocial ramifications. This manuscript examined the impact of breast cancer on women's body image, including women of color and lesbians. The information was contextualized through the application of feminist theory principles. Interventions and implications for breast cancer survivors (BCS) were discussed utilizing feminist theory.